Youth Voice and the Promise and Peril of Affirmative Governmentality: An Analysis of New York City’s Borough Student Advisory Councils - Donnell, Hillary R (2019)
This study addresses civil society and the state’s shifting approach towards the incorporation of youth in governmental decision-making since the 1990s, and the recent ascendance of youth voice councils as a method of civic engagement. It uses the New York City Youth Leadership Council Initiative and the Borough Student Advisory Councils as case studies. Relying on the author’s ethnographic participant observation and youth-voice frameworks, the paper provides an analysis of the individual, organizational and systems level effects of the New York Department of Education’s BSAC program. Further, the paper discusses affirmative governmentality as a lens through which to critically examine the use of youth councils and youth voice initiatives. The NYC case suggests that, even as youth voice expands in municipal government, it does so in narrow, scripted ways-- forwarding a model of affirmative governmentality in the process. The analysis raises questions about the opportunities and limits of youth councils as strategies for meaningful youth politicization